Simultaneous enhancement of mechanical properties at room and elevated temperatures in Mg-RE alloy via twin-induced recrystallization and LPSO precipitation - Jiawen Zhou; Xiaoru Zhang; Daqing Fang; Hongxiang Zong; Xiangdong Ding; Jun Sun (Journal of Materials Research and Technology)
Understanding the microstructure evolution of long period stacking ordered (LPSO) phases in deformation-twinned Mg-RE alloys and its impact on mechanical performance remains limited. This study introduces a novel processing strategy involving multi-pass cold rolling to create a preset twin network, followed by aging treatment. The strategy investigates the interplay between twin-induced recrystallization and the precipitation of 14H-LPSO phases in Mg-8.5Gd-3Y-2Cu-0.5Zr (wt.%) alloys. This interaction promotes the formation of recrystallized grain regions containing a finely dispersed distribution of 14H-LPSO phases, with the kinetics of precipitation governed by locally confined space and activation volume conditions. Mechanical testing reveals significant enhancements in performance, with room-temperature ductility increasing from 3.6 % to 13.5 %, a 2.75-fold enhancement, primarily attributed to the occurrence of recrystallization and the fine dispersion of 14H-LPSO phases, which effectively reduce the barriers to dislocation slip. Furthermore, the high-temperature ultimate tensile strength improves from 186 MPa to 207 MPa, which is ascribed to the thermal stability of the LPSO phase and its grain boundary pinning effect. These results provide new insights into microstructural design strategies for developing high-performance, heat-resistant magnesium alloys.